2016
DOI: 10.1097/ta.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Imaging before transfer to designated pediatric trauma centers exposes children to excess radiation

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…26 Regarding the risk of CT scans in children, as required by 2 patients in this current paper, the literature advises to do CT scans on children in pediatric hospitals becuase they substantially reduce the radiation received by the children. [27][28][29] Although the radiation dose from a single CT scan is relatively low, when adult-sized imaging techniques are used, children receive a higher radiation dose. 30 The children's hospital where the interventions took place in this study employs only specialized pediatric radiologists who strictly follow the "as low as reasonably achievable" principle, using pediatric imaging protocols and the newest scanner technology.…”
Section: Discussionmentioning
confidence: 99%
“…26 Regarding the risk of CT scans in children, as required by 2 patients in this current paper, the literature advises to do CT scans on children in pediatric hospitals becuase they substantially reduce the radiation received by the children. [27][28][29] Although the radiation dose from a single CT scan is relatively low, when adult-sized imaging techniques are used, children receive a higher radiation dose. 30 The children's hospital where the interventions took place in this study employs only specialized pediatric radiologists who strictly follow the "as low as reasonably achievable" principle, using pediatric imaging protocols and the newest scanner technology.…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous studies have shown that patients imaged at community-based RFs are exposed to higher CT scan radiation dosages when compared with patients imaged at PTCs. 6,12 These studies analyzed patients imaged in the early 2010s, shortly after the "Image Gently" campaign to reduce pediatric CT radiation dose. Our study sought to determine whether such differences in CT scan-related radiation dosages have persisted as well as to see if there are any identifiable characteristics of either patients or RFs that may be associated with increased radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, there have been studies from several institutions around the country demonstrating that dedicated children's hospitals have been more successful in implementing lower CT radiation dosing in pediatric patients when compared with AGHs for a broad range of clinical indications, including trauma. [26][27][28][29][30][31] This remains true even if the referring institution is a trauma center. 32 Indeed, when we split our AGHs into trauma centers and non-trauma centers, we found a similarly significant dose reduction for both.…”
Section: Discussionmentioning
confidence: 99%